Carbon monoxide alleviates senescence in diabetic nephropathy by improving autophagy. (7th May 2021) - Chen, Li; Mei, Guibin; Jiang, Chunjie; Cheng, Xueer; Li, Dan; Zhao, Ying; Chen, Huimin; Wan, Cheng; Yao, Ping; Gao, Chao; Tang, Yuhan
Abstract: Objectives: Senescence, characterized by permanent cycle arrest, plays an important role in diabetic nephropathy (DN). However, the mechanism of renal senescence is still unclear, and the treatment targeting it remains to be further explored. Materials and Methods: The DN mice were induced by HFD and STZ, and 3 types of renal cells were treated with high glucose (HG) to establish in vitro model. Senescence‐related and autophagy‐related markers were detected by qRT‐PCR and Western blot. Further, autophagy inhibitors and co‐immunoprecipitation were used to clarify the mechanism of CO. Additionally, the specific relationship between autophagy and senescence was explored by immunofluorescence triple co‐localization and ELISA. Results: We unravelled that senescence occurred in vivo and in vitro, which could be reversed by CO. Mechanistically, we demonstrated that CO inhibited the dysfunction of autophagy in DN mice partly through dissociating Beclin‐1‐Bcl‐2 complex. Further results showed that autophagy inhibitors blocked the improvement of CO on senescence. In addition, the data revealed that autophagy regulated the degradation of senescence‐related secretory phenotype (SASP) including Il‐1β, Il‐6, Tgf‐β and Vegf . Conclusions: These results suggested that CO protects DN mice from renal senescence and function loss via improving autophagy partly mediated by dissociating Beclin‐1‐Bcl‐2 complex, which is possibly ascribed to the degradation of SASP. These findings bring new ideas for the prevention and treatment of DN and the regulation of senescence. Abstract : In diabetic nephropathy, senescent cells were accumulated, which may accelerate disease progression through senescence‐related secretory phenotype (SASP). Carbon monoxide activated autophagy by dissociating Beclin‐1‐Bcl‐2 complexe, and restore lysosomal function to improve autophagy flow, enabling autophagosomes to encapsulate some SASP and deliver it to lysosome for degradation. Thus, the reversion of SASP from secretion to degradation prevented senescence and subsequently improved DN.